Post-initiation activities of the archaeal RNA polymerase in a chromatin landscape - Sanders, Travis James, author; Santangelo, Thomas, advisor; Hansen, Jeffrey C., committee member; Peersen, Olve B., committee member; Ben-Hur, Asa, committee member (Colorado State University. Libraries, 2020)
The machineries that control transcription initiation and elongation in Archaea and Eukarya are highly homologous. These similarities support the prevailing evolutionary theory of Archaea being the progenitor of Eukarya. Due to the retention of a core transcription apparatus, while lacking complexities of the eukaryotic counterpart, archaeal systems offer the unique potential to study and characterize the basic protein components necessary for transcription. Transcription termination was less well understood in both Archaea and Eukarya. Shared homology of the initiation and elongation phases argued for a homologous method of termination in Archaea and Eukarya. Additionally, both the archaeal and eukaryotic transcription apparatuses are frequently impeded by histone proteins bound to DNA. Like the transcription complex, archaeal histones are a simplified mirror to eukaryotic histones, permitting evaluation of all steps in the transcription cycle in the context of a chromatin landscape. This thesis summarizes the core molecular machineries involved in the regulation of archaeal transcription during elongation and termination in the greater context of archaeal histone-based chromatin. Thus, the discoveries made have contributed to both the transcription and chromatin fields by providing mechanistic details of the core, conserved transcription apparatus in the framework of evolution.
Keywords: chromatin; RNA; transcription; histones; Archaea; RNA polymerase